Antioxidant properties of anthocyanidins, anthocyanidin-3-glucosides and respective portisins - Joana Azevedo (2010)
The study of the antioxidants properties of three classes of pigments, namely anthocyanidins (cyanidin-Cy, delphinidin-Dp and malvidin-Mv), anthocyanidin-3-glucosides (Cy-3-gluc, Dp-3-gluc and Mv-3-gluc), and portisins (Cy-pt, Dp-pt and Mv-pt) was carried out. The aim was to evaluate the relationship between the structure antioxidant properties of individual anthocyanins and respective derivative pigments. The ability of these compounds to inhibit lipid peroxidation in a liposome membrane system was examined by monitoring oxygen consumption and the antiradical and reducing capacities were determined using the DPPH and FRAP assay, respectively. All compounds tested showed antiradical and reducing properties. These features seemed to increase with the presence of catechol and pyrogallol groups in ring B of anthocyanidin-3-glucosides and respective aglycones. The results obtained for portisins are very likely to be related with their unique structural features. The flavanol moiety of the Compounds structure seems to be crucial for the antiradical properties, whilst their reducing ability was only evident for the portisin derived from malvidin. This outcome Could be due to some of the structural features of these pigments as they are complex structures and may have several different conformations in solution. The antioxidant protection towards lipid peroxidation increased with the overall hydrophobicity of the compounds. This feature is related to the location of the antioxidant on the liposome surface vs. water phase. Among the pigments tested, portisins showed the higher effect in preventing lipid peroxidation of soybean phosphatidylcholine liposomes, especially the portisin derived from Cy. This outcome could be due to the presence of two o-catechol groups in the structure of this compound.